Extracellular Mitochondria Activate Microglia and Contribute to Neuroinflammation in Traumatic Brain Injury - Chaonan Zhang; Chuan Liu; Fanjian Li; Mutian Zheng; Yafan Liu; Lei Li; Huaijin Yang; Shu Zhang; Chongjin Wang; Hongtao Rong; Hui Guo; Ying Li; et al. (Neurotoxicity Research, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

Plasma Exo-miRNAs Correlated with AD-Related Factors of Chinese Individuals Involved in Aβ Accumulation and Cognition Decline - Lifang Wang; Hefu Zhen; Yuzhe Sun; Shuang Rong; Benchao Li; Zhijie Song; Zhili Liu; Zhiming Li; Jiahong Ding; Huanming Yang; Xiuqing Zhang; Haixi Sun; et al. (Molecular Neurobiology, 2022)
Numerous studies have investigated the risk factors of Alzheimer’s disease (AD); however, AD-risk factors related miRNAs were rarely reported. In this study, AD-risk factor related miRNAs of 105 Chinese individuals (45 AD patients and 60 cognitively normal controls) were investigated. The results showed that Hsa-miR-185-5p, Hsa-miR-20a-5p, and Hsa-miR-497-5p were related to AD and education, Hsa-miR-185-5p, Hsa-miR-181c-5p, Hsa-miR-664a-3p, Hsa-miR-27a-3p, Hsa-miR-451a, and Hsa-miR-320a were related to AD and depression. Target prediction of above miRNAs showed that these miRNAs were involved in the generation and clearance of amyloid-beta (Aβ), important molecules related to cognition, and disease-activated microglia response to AD. It is worth noting that Hsa-miR-185-5p was related to both education and depression, whose decreased expression pattern in AD patients was alleviated by education and enhanced by depression, and participates in Aβ generation and accumulation. Our results indicated that certain education and depression factors can contribute to AD progression by modulating miRNA expression, implying that preventive interventions might alter AD progression in Chinese patients.

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Homozygous missense mutation in CCDC155 disrupts the transmembrane distribution of CCDC155 and SUN1, resulting in non-obstructive azoospermia and premature ovarian insufficiency in humans - Huan Wu; Xin Zhang; Rong Hua; Yuqian Li; Li Cheng; Kuokuo Li; Yiyuan Liu; Yang Gao; Qunshan Shen; Guanxiong Wang; Mingrong Lv; Yuping Xu; et al. (Human Genetics, 2022)

Concentrations, distribution, and risk assessment of endosulfan residues in the cotton fields of northern Xinjiang, China - Yang Zhang; Rong Guo; Yang Li; Mingyu Qin; Jingquan Zhu; Zhihong Ma; Yong Ren (Environmental Geochemistry and Health, 2022)

HOXD11 upregulates JAM-A and exerts oncogenic properties via NF-κB signaling pathway in esophageal squamous cell carcinoma - Rong Xiong; Qiongxian Long; Xuqian Zhang; Jun Xu; Yanqun Liu; Li Xiong; Siyun Yang; Gang Feng; Guiqing Song; Kang Liu (Human Cell, 2022)

Induced mutation in ELONGATED HYPOCOTYL5 abolishes anthocyanin accumulation in the hypocotyl of pepper - Rong Chen; Can Yang; Hu Gao; Chunmei Shi; Zhiying Zhang; Guangyu Lu; Xinyan Shen; Yaping Tang; Feng Li; Yongen Lu; Bo Ouyang (Theoretical and Applied Genetics, 2022)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Tetramethylpyrazine protects neural stem cells against sevoflurane-induced toxicity through Akt/GSK-3β pathway - Yan Feng; Kui Wang; Ning Wang; Pengyu Jia; Lei Zhang; Haozheng Yuan; Pan Lu; Yang Lu; Hong Zhang; Rong Li; Yan Zhang; Qianqian Li; et al. (Metabolic Brain Disease, 2022)

Identification of resistance of Guangxi (Oryza rufipogon Griff.) to white-backed planthopper with stem evaluation method - Xin-ying Guo; Xuan Wang; Liang Luo; Yao-yu Fang; Kai-chong Teng; Neng Zhao; Jin-lian Yang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Genetic Resources and Crop Evolution, 2022)

Physiology, metabolism, antibiotic resistance, and genetic diversity of Harveyi clade bacteria isolated from coastal mariculture system in China in the last two decades - Hao Kang; Yongxiang Yu; Meijie Liao; Yingeng Wang; Guanpin Yang; Zheng Zhang; Bin Li; Xiaojun Rong; Chunyuan Wang (Frontiers in Marine Science, 2022)
Vibrio bacteria, particularly members of the Harveyi clade, are the most important pathogens of aquatic organisms that cause significant economic losses in the world. It is difficult to provide specific data on taxa of the Harveyi clade for biological research and prevention strategies. Therefore, we conducted an extensive phenotypic and antibiotic resistance study, as well as phylogenetic and molecular typing of 192 isolates of the Harveyi clade collection from 2000 to 2020 with a typical interannual difference from a coastal area in China. The isolates had a significant interspecific genetic and antibiotic resistance diversity. Based on the multilocus sequence analysis (MLSA) of housekeeping genes ( gyrB , pyrH , recA , and atpA ), 192 Harveyi clade isolates were rapidly and accurately classified into 10 species. The population of these isolates was composed of 95 sequence types (STs), of which 92 STs were newly identified, indicating a high degree of genetic diversity. ST327 ranked first, accounting for 11.5% of the total number of isolates (22 out of 192), followed by ST215 with 6.25%, while 63 STs included single isolates. At the metabolic level, the physiological and biochemical experiments revealed that all the Harveyi clade isolates were positive for oxidase and negative for melibiose. The isolates showed a varied tolerance to 11 antibiotics. No isolates were resistant to neomycin. The percentages of sulfadimidine-resistant strains (61 out of 192), sulfadiazine (44 out of 192), sulfamonomethoxine (44 out of 192), sulfamethoxazole (33 out of 192), thiamphenicol (34 out of 192), ciprofloxacin (52 out of 192), and enrofloxacin (31 out of 192) were 31.77%, 22.92%, 22.92%, 17.19%, 17.71%, 27.08%, and 16.15%, respectively. A proportion of 61.8% of the isolates presented a multiple antibiotic resistance index (MARI) lower than 0.1, indicating that the risk of antibiotic resistance transmission of most of the Harveyi clade is low in mariculture systems in China. These results provide substantial data to support further studies on the identification and genetic and metabolic diversity of Harveyi clade isolates in mariculture systems in China.

Synthesis and in vitro biological evaluation of novel dendrocandin analogue as potential anti-tumor agent - Jing-Yun Yan; Hao-Nan Yang; Ning Yang; Yin-Rong Xie; Xiu-Li Sun; Ye-Wei Huang; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Natural Product Research, 2022)

Progranulin, a moderator of estrogen/estrogen receptor α binding, regulates bone homeostasis through PERK/p-eIF2 signaling pathway - Yuyou Yang; Naibo Feng; Li liang; Rong Jiang; Yiming Pan; Nana Geng; Mengtian Fan; Xiaoli Li; Fengjin Guo (Journal of Molecular Medicine, 2022)

Microplastic prevalence in marine fish from onshore Beibu Gulf, South China Sea - Jayamini Bimali Koongolla; Lang Lin; Chang-Ping Yang; Yun-Feng Pan; Heng-Xiang Li; Shan Liu; Xiang-Rong Xu (Frontiers in Marine Science, 2022)
In recent years, microplastics have been widely detected in marine fish and may pose potential risks to fish and human health. Even though microplastic pollution is a critical issue, it represents as yet non-quantified threat for some context in the marine environment. In this study, 271 individuals comprising 32 species of marine fish collected from Beibu Gulf were examined for microplastic prevalence, with an aim to provide data on the abundance, physical classification, and chemical characterization of microplastics in the great bay along South China Sea. The results showed that the occurrence rate of microplastics was 93.7%, and the average abundance of microplastics was 1.02 ± 0.18 items per individual (ranging from 0.03 to 4.00 items per individual). Microplastic accumulation was observed with a great variation in different species, body sizes, living habitats, and feeding habits of marine fishes. The dominant polymers identified by μ-FTIR were polyethylene terephthalate and polypropylene. Fibers, smaller sizes (<1 mm), and transparent color were the major characteristics of the detected microplastics, which might be important factors affecting the bioaccumulation. The present study revealed that microplastics in marine fish is a widespread issue in onshore Beibu Gulf.

Functional divergence of oligoadenylate synthetase 1 (OAS1) proteins in Tetrapods - Xiaoxue Wang; Jiaxiang Hu; Linfei Song; Enguang Rong; Chenghuai Yang; Xiaoyun Chen; Juan Pu; Honglei Sun; Chuze Gao; David W. Burt; Jinhua Liu; Ning Li; et al. (Science China Life Sciences, 2022)

Selenium Deficiency Induces Autophagy in Chicken Bursa of Fabricius Through ChTLR4/MyD88/NF-κB Pathway - Ruili Zhang; Qing Liu; Rong Guo; Di Zhang; Yang Chen; Guangxing Li; Xiaodan Huang (Biological Trace Element Research, 2022)

Bmal1- and Per2-mediated regulation of the osteogenic differentiation and proliferation of mouse bone marrow mesenchymal stem cells by modulating the Wnt/β-catenin pathway - Jiawen Zheng; Lanxin Zhang; Zhen Tan; Qing Zhao; Xiaoyu Wei; Yuqing Yang; Rong Li (Molecular Biology Reports, 2022)

Prediction of the sea buckthorn AQP gene structure and its spatiotemporal expression pattern under drought stress - Dan Zhang; Nanxiang Yang; Jiawei Dong; Cheng Wang; Qiangfeng Li; Rong Wang; Zhipeng Feng; Dejuan Xie; Guisheng Ye; Yuhua Ma (Journal of Plant Biochemistry and Biotechnology, 2022)

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

Urinary phthalate metabolites in pregnant women: occurrences, related factors, and association with maternal hormones - Wei Wu; Zhi-li Ma; Fang Yang; Ping Wu; De-xin Zhang; Rong Zeng; Dan-ling Sun; Liu Cao (Environmental Science and Pollution Research, 2022)

γ-Cyclodextrin metal–organic framework as a carrier to deliver triptolide for the treatment of hepatocellular carcinoma - Zhe Li; Gang Yang; Rong Wang; Yuanyuan Wang; Jing Wang; Meng Yang; Chunai Gong; Yongfang Yuan (Drug Delivery and Translational Research, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Cassiterite oxygen isotopes in magmatic-hydrothermal systems: in situ microanalysis, fractionation factor, and applications - Yang Li; Sheng He; Rong-Qing Zhang; Xian-Wu Bi; Lian-Jun Feng; Guo-Qiang Tang; Wen-Zhong Wang; Fang Huang; Xian-Hua Li (Mineralium Deposita, 2022)

The Predictability of Ocean Environments that Contributed to the 2020/21 Extreme Cold Events in China: 2020/21 La Niña and 2020 Arctic Sea Ice Loss - Fei Zheng; Ji-Ping Liu; Xiang-Hui Fang; Mi-Rong Song; Chao-Yuan Yang; Yuan Yuan; Ke-Xin Li; Ji Wang; Jiang Zhu (Advances in Atmospheric Sciences, 2022)
Several consecutive extreme cold events impacted China during the first half of winter 2020/21, breaking the low-temperature records in many cities. How to make accurate climate predictions of extreme cold events is still an urgent issue. The synergistic effect of the warm Arctic and cold tropical Pacific has been demonstrated to intensify the intrusions of cold air from polar regions into middle-high latitudes, further influencing the cold conditions in China. However, climate models failed to predict these two ocean environments at expected lead times. Most seasonal climate forecasts only predicted the 2020/21 La Niña after the signal had already become apparent and significantly underestimated the observed Arctic sea ice loss in autumn 2020 with a 1–2 month advancement. In this work, the corresponding physical factors that may help improve the accuracy of seasonal climate predictions are further explored. For the 2020/21 La Niña prediction, through sensitivity experiments involving different atmospheric–oceanic initial conditions, the predominant southeasterly wind anomalies over the equatorial Pacific in spring of 2020 are diagnosed to play an irreplaceable role in triggering this cold event. A reasonable inclusion of atmospheric surface winds into the initialization will help the model predict La Niña development from the early spring of 2020. For predicting the Arctic sea ice loss in autumn 2020, an anomalously cyclonic circulation from the central Arctic Ocean predicted by the model, which swept abnormally hot air over Siberia into the Arctic Ocean, is recognized as an important contributor to successfully predicting the minimum Arctic sea ice extent.

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Pulsed exsolution of magmatic ore-forming fluids in tin-tungsten systems: a SIMS cassiterite oxygen isotope record - Yang Li; Rong-Qing Zhang; Sheng He; Massimo Chiaradia; Xian-Hua Li (Mineralium Deposita, 2022)

Effect of Fertilization Regimes and Seasonal Change on nosZ-Denitrifying Bacterial Community in a Double-Rice Paddy Field - Jiangwen Nie; Yong Zhou; Wei Yang; Shaoqiu Li; Haoxuan Li; Jianwei Wu; Chengwei Li; Xiaoyuan Yan; Rong Zhu; Bo Zhu; Zhangyong Liu (Journal of Soil Science and Plant Nutrition, 2022)

Study on the impact of comprehensive urbanization on urban civil building CO2 emissions in China - Rong Guo; Nan Li; Hailin Mu; Ming Zhang; Xiyue Yang; Yixuan Han; Rongkang Yao; Zhihao Shao (Environmental Science and Pollution Research, 2022)

Sediment Resuspension as a Major Contributor to Sinking Particles in the Northwestern South China Sea: Evidence From Observations and Modeling - Lihua Ran; Wentao Ma; Martin G. Wiesner; Yuntao Wang; Jianfang Chen; Lanlan Zhang; Zhi Yang; Jingjing Zhang; Hongliang Li; Jian Ren; Rong Xiang; Erick Fredj (Frontiers in Marine Science, 2022)
The lateral advection of sinking particles is a well-known phenomenon in the South China Sea (SCS) and has a significant impact on the estimation of the efficiency of the biological carbon pump. However, little is known about the sources and pathways of sinking particles. Here, we present benthic and freshwater diatom fluxes and relative abundances collected by a sediment trap deployed at a water depth of 1,000 m and more than 500 m above the seafloor in the northwestern SCS, indicating that laterally transported resuspended sediment accounts for a significant part of the particle flux to the deep sea. A Lagrangian particle tracking model (LPTM) revealed that the resuspended particles likely originated from the neighboring continental slope, approximately 12–145 km to the west of the study site. Sediment trap observations and the LPTM together indicated that the impact of resuspended sediment occurred mainly in the deep water, and especially strong sediment resuspension was related to summer monsoon-induced coastal upwelling. The results suggest that particle resuspension has an important impact on the biological pump as well as on paleoenvironmental reconstructions of the SCS.

Neoflavonoids from the heartwood of Dalbergia melanoxylon - Meng-fei Wang; Guang-qiang Ma; Feng Shao; Rong-hua Liu; Lan-ying Chen; Yang Liu; Li Yang; Xiao-wei Meng (Natural Product Research, 2022)

A new prenylated 3-benzoxepin derivative with anti-influenza A virus activity from Elsholtzia penduliflora - Lu Zhang; Linyao Yang; Rong-Tao Li; Fei Yu; Jindong Zhong (Natural Product Research, 2022)

Activation of Autophagy Ameliorates Age-Related Neurogenesis Decline and Neurodysfunction in Adult Mice - Na Yang; Xueqin Liu; Xiaojie Niu; Xiaoqiang Wang; Rong Jiang; Na Yuan; Jianrong Wang; Chengwu Zhang; Kah-Leong Lim; Li Lu (Stem Cell Reviews and Reports, 2022)

Do driving restriction policies effectively alleviate smog pollution in China? - Lan Yi; Zhi-rong Kang; Li Yang; Mohammad Musa; Fei Wang (Environmental Science and Pollution Research, 2022)

Selenium Deficiency Causes Inflammatory Injury in the Bursa of Fabricius of Broiler Chickens by Activating the Toll-like Receptor Signaling Pathway - Yu Bai; Ruili Zhang; Qing Liu; Rong Guo; Guangxing Li; Bin Sun; Di Zhang; Yang Chen; Xiaodan Huang (Biological Trace Element Research, 2022)

Flavobacterium proteolyticum sp. nov., isolated from aquaculture water - Juan Du; Yang Liu; Tao Pei; Anzhang Li; Ming-Rong Deng; Honghui Zhu (Archives of Microbiology, 2022)

The anticancer potential of the dietary polyphenol rutin: Current status, challenges, and perspectives - Arakkaveettil Kabeer Farha; Ren-You Gan; Hua-Bin Li; Ding-Tao Wu; Atanas G. Atanasov; Khalid Gul; Jia-Rong Zhang; Qiong-Qiong Yang; Harold Corke (Critical Reviews in Food Science and Nutrition, 2022)

Genetic diversity of Lathyrus sp collected from different geographical regions - Md. Mosiur Rahman; Md. Ruhul Quddus; Md. Omar Ali; Rong Liu; Mengwei Li; Xin Yan; Guan Li; Yishan Ji; Md. Monoar Hossain; Chenyu Wang; Ashutosh Sarker; Tao Yang; et al. (Molecular Biology Reports, 2022)

Exosomal microRNA-125a-3p from human adipose-derived mesenchymal stem cells promotes angiogenesis of wound healing through inhibiting PTEN - Li Pi; Li Yang; Bai-Rong Fang; Xian-Xi Meng; Li Qian (Molecular and Cellular Biochemistry, 2022)